Uncertainly-Based Critical Nursing Model on Family of Family Needs in Bangil General Hospital, Pasuruan, Indonesia - Tanty Wulan Dari; Moch Bahrudin (Institute of Medico-legal Publications Pvt Ltd, 2021)
Holistic care in the intensive unit should be provided for patients and their families. The patient’s familywaiting in the intensive care room may experience uncertainty. Not only because of the unfamiliar treatmentrooms, but also because of the health workers who are strangers to them and speak with medical terms. Theobjective of this research is to develop the CCFN (Critical Care Family Need) Nursing Model towards theadaptation of the patient’s family in the Intensive Care Unit (ICU). The research was conducted with anexplanatory design. The population in this study was patients’ most influential family member in makingdecisions (related to patients’ care and medication) at Bangil General Hospital in 2020. The sample size was105 with consecutive sampling technique. Research variables included: factors related to the patient, familypsychology, health services, family needs and family adaptation. PLS testing was performed, then FGD wasdone to strengthen the statistical model. Results showed a different finding compared to the initial concept,where there the families’ thinking capacity p showed no significant effect on the families’ coping factor.The families’ coping factor showed no significant effect on the critical care family need (CCFN). However,family coping factor showed a significant effect on family adaptation factor. In conclusion, there are twoindicators that can explain the fulfilling of family needs factors, namely indicators of mental support fromhealth workers and their closeness to patients. Calmness of family during discussion with health workers, aswell as enthusiasm felt by the patient’s family, are things that must be noted, so that the family adaptationprocess occurs optimally.